Analysis of the Utilization of social media and Business Communication on the Impact of the Covid-19 Pandemic on Talent Master of Ceremony (MC) - Aldo Ferdian Putra; Ridzki Rinanto Sigit; Jamalullail Jamalullail (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The impact of the Covid-19 pandemic on agency services has made a lack of income, and even the almost absence of a structured event schedule makes companies have to figure out how to run their business with the availability of costs that are still there. Not only service companies but also those affected by it and even talents who are in management. MC talents using social media on Instagram and others to communicate with clients is the most ideal way to understand the interaction of correspondence by answering questions. This research was conducted using a descriptive qualitative research method, based on marketing communication through social media by Laswell. In the process of using social media where an MC can promote himself to the community, so that the public can know about the role of being an MC. And with the use of social media is as a place of communication to the wider community In communicating to the public so that the public recognizes themselves, which is one way of communicating using social media, where by using social media an MC can communicate, one of which is live Instagram, posting photos or doing videos. The existence of social media can make it easier for any entrepreneur to be able to promote himself, where the majority of people around the world use social media for entertainment and as a means of communication and appreciating themselves. In addition, talents who are outside the Aldho_Entertainment agency can also follow the way talents in Aldho_Entertainment agency by utilizing social media to promote themselves to the wider community to be better known. Talents and agencies are expected to work well together to create a good job and use what social media talents can use to train themselves again and to communicate to the wider community.